2019
DOI: 10.1038/s41390-019-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher fat mass and fat mass accretion during the first six months of life in exclusively breastfed infants

Abstract: BACKGROUND: Early nutrition influences infant growth and body composition, which may play a role in the infant's metabolic programming. Breastfed infants appear to have higher fat mass than formula-fed infants, but most comparisons have been crosssectional, and evidence is scarce. The aim of this study was to describe fat mass and fat mass accretion during the first six months of life and evaluate differences by type of feeding (OMS). METHODS: Prospective cohort of healthy pregnant women and their infants (Mex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
(57 reference statements)
0
20
1
Order By: Relevance
“…Reportedly, breastfed infants have higher fat accretion compared with formula-fed [ 10 , 42 ] and non-exclusively breastfed infants [ 43 ], speculating that substantial fat accrual during this period of active growth may be protective against obesity later in life. As specific location of fat accretion may determine higher metabolic risk [ 44 ], it is imperative to investigate if higher fat accretion in the abdominal area in breastfed infants means more metabolic risk, and if development of these fat depots is independently regulated in this population and affected by nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, breastfed infants have higher fat accretion compared with formula-fed [ 10 , 42 ] and non-exclusively breastfed infants [ 43 ], speculating that substantial fat accrual during this period of active growth may be protective against obesity later in life. As specific location of fat accretion may determine higher metabolic risk [ 44 ], it is imperative to investigate if higher fat accretion in the abdominal area in breastfed infants means more metabolic risk, and if development of these fat depots is independently regulated in this population and affected by nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, except for a modest increase in MUAC, the differences for LAZ, WAZ, and WLZ were not statistically significant. These findings could be due to the effect of exclusive or predominant breastfeeding that promotes higher accretion of fat mass during the first six months of life [40]. Moreover, not only breastfeeding behaviour but also intrauterine growth retardation contributes considerably to infant growth faltering, and growth faltering is also more prominent after six months of age when infants start complementary feeding [41].…”
Section: Discussionmentioning
confidence: 99%
“…Another study including a total of 158 infants (72 exclusively breastfed and 86 exclusively formula-fed) reported that body composition was similar between the two groups at enrolment, but fat-free mass at 4 months and the fat-free mass changes between enrolment and 4 months were higher in formula-fed infants than breastfed ones (16) . In contradistinction, another study showed that EBF infants showed a significantly higher fat mass accretion (17) . Hence there is considerable controversy regarding fat mass accretion between breastfed and formula fed.…”
Section: Discussionmentioning
confidence: 91%